The Effect of Competency, Motivation and Discipline on Employee Performance: The Case of Population and Civil Registration Office of Palembang City - Andriani, Septi; Idris, Muhammad; Choiriyah, Choiriyah (International Journal of Marketing & Human Resource Research, 2025)
This study aims to determine 1) the Effect of Competence, Motivation, and Work Discipline on Employee Performance at the Population and Civil Registration Service of Palembang City. 2) The Effect of Competence on Employee Performance at the Population and Civil Registration Service of Palembang City. 3) The Influence of Motivation on the Performance of Employees of the Population and Civil Registration Service of Palembang City. 4) The Influence of Work Discipline on the Performance of Employees of the Population and Civil Registration Service of Palembang City. This type of research is Associative. The variables used by researchers include Competence, Motivation, Work Discipline, and Performance. The population of this study consisted of all Employees of the Population and Civil Registration Service of Palembang City, and the sample size in the study amounted to 101 employees. The sampling technique used was Proportionate Stratified Random Sampling. The data used in this study are primary data collected through a questionnaire. The data analysis technique used is multiple linear regression. The results of this study indicate that: 1) Competence, Motivation, and Work Discipline have a significant effect on the Performance of Employees of the Population and Civil Registration Service of Palembang City. 2) Competence has a significant effect on the Performance of Employees of the Population and Civil Registration Service of Palembang City. 3) Motivation significantly influences the performance of employees at the Palembang City Population and Civil Registration Service. 4) Work discipline significantly influences the performance of employees at the Palembang City Population and Civil Registration Service.